ADAB GURU DAN MURID DALAM KITAB ADABUL A’LIM WAL MUTAA’ALLIM DAN IMPLEMENTASINYA DI STID AL FURQON PONOROGO - Rizwan Dongoran; Mohammad Yoga Adji Pangestu; Happy Susanto; Sigit Dwi Laksana (LPPM IAD Probolinggo, 2025)
Education is the capital for the formation of a civilization, while adab education is an important process in forming generations of warriors for this civilization. Islam views that adab education is something that must be continuously taught to humans so that they are able to exemplify what was exemplified by the Prophet Muhammad. then thus as an educational institution must strive to teach Adab to its students. To discuss in more detail the author takes the discussion by examining the book Adabula'lim Walmuta'allim and its implementation at STID Al Furqon Ponorogo, which aims to find out: (1) How is the concept of adab teachers and students in the book Adabul'alim Waal muta'allim; (2) How is the implementation and results of the concept of teacher and student adab in the book Adabul'alim Waal muta'allim at STID Al Furqon. This research is a library research and field research using descriptive methods. Primary data as the main source, namely the bookAdab al'alim Waalmuta'allim and secondary data is literature that is relevant to research. As for analyzing documentation data, using data analysis methods, then drawing conclusions, so that results are obtained that are accurate and easy to understand. The results of this study related to teacher and student etiquette, namely: Teacher etiquette (1) The teacher educates students to understand religion; (2) Sincere teachers teach knowledge to students; (3) The teacher loves students as he loves himself; (4) The teacher gives clearly; (5) The teacher enthusiastically teaches students; (6) The teacher gives good advice to students; (7) The teacher treats students fairly; (8) Maintain authority before students; (9) The teacher pays attention to students; (10) Calling students with good names. Student etiquette, namely: (1) Students are serious in learning; (2) Students obey the teacher; (3) Students must glorify the teacher; (4) Students always pray for their teacher; (5) Students must be patient when the teacher is angry; (6) Students must ask permission if they want to leave the lesson; (6) Sitting in front of the teacher respectfully and solemnly when studying; (7) speak well to the teacher; (8) If the teacher conveys the same lesson, students must listen even though they have studied it; (9) Appreciate the teacher's gift. The results of the implementation of this adab education are quite good for teachers and students because they are directly felt by the community. In its implementation, STID AL Furqon applies this concept through the curriculumArkanul Bi'tsah with learning in the classroom, outside the classroom and outside the campus. Keywords : manners; Book of Adabul A'lim Wal Mutaa'allim; implementation